Endometrial stem/progenitor cells: Properties, origins, and functions - In-Sun Hong (Genes and Diseases, 2023)
The endometrium is the inner mucosal lining of the uterus that undergoes extensive cyclic growth, regeneration, differentiation, and shedding throughout the menstrual cycle in response to steroid hormones. It repeatedly undergoes approximately 450 cycles of degeneration and regeneration in a woman's lifetime. Endometrial abnormalities can be associated with repeated embryo implantation failure, recurrent spontaneous abortion, and other physiological features responsible for female infertility. This significant regenerative capacity may occur as a result of tissue-resident stem cell populations within the endometrium. Indeed, the existence of endometrial stem cells was only observed in humans and rodents through several isolation and characterization methods in the last few years. Although endometrial stem cells share various biological characteristics with other types of mesenchymal stem cells, they also show some differences in phenotype, self-renewal, and multilineage differentiation potential. Extensive studies over many years on endometrial stem cells will provide new insights into the physiology and mechanisms underlying various gynaecological diseases related to endometrial abnormalities such as female infertility, endometriosis, and endometrial cancer. Here we summarized recent studies about cellular origins and biological characteristics of endometrial stem cells. We also reviewed various recent studies to improve our understanding of their physiological roles. Many preclinical studies on their potential therapeutic applications to various endometrial diseases that could lead to reproductive dysfunction were also reviewed.